Adjuvants influence the immune cell populations present at the injection site granuloma induced by whole-cell inactivated paratuberculosis vaccines in sheep - Criado, Miguel; Reyes, Luis E.; Marín, Juan F. García; Gutiérrez-Expósito, Daniel; Zapico, David; Espinosa, José; Pérez, Valentín (Frontiers in Veterinary Science, 2024)
Vaccination is the most effective tool for paratuberculosis control. Currently, available vaccines prevent the progression of clinical disease in most animals but do not fully protect them against infection and induce the formation of an injection site granuloma. The precise mechanisms that operate in response to vaccination and granuloma development, as well as the effect that adjuvants could trigger, have not been fully investigated. Therefore, this study aimed to investigate the injection site granulomas induced by two inactivated paratuberculosis vaccines, which differ in the adjuvant employed. Two groups of 45-day-old lambs were immunized with two commercially available vaccines—one (n = 4) with Gudair® and the other (n = 4) with Silirum®. A third group (n = 4) was not vaccinated and served as control. The peripheral humoral response was assessed throughout the study by a commercial anti-Mycobacterium avium subspecies paratuberculosis (Map) antibody indirect ELISA, and the cellular immune response was assessed similarly by the IFN-γ release and comparative intradermal tests. The injection site granulomas were measured during the experiment and sampled at 75 days post-vaccination (dpv) when the animals were euthanized. The tissue damage, antigen and adjuvant distribution, and the presence and amount of immune cells were then determined and assessed by immunohistochemical methods. Antibodies against Map antigens; a general macrophage marker (Iba1), M1 (iNOS), and M2 (CD204) macrophages; T (CD3), B (CD20), and γδ T lymphocytes, proteins MHC-II and NRAMP1, and cytokines IL-4, IL-10, TNF, and IFN-γ were employed. Silirum® elicited a stronger peripheral cellular immune response than Gudair®, while the latter induced larger granulomas and more tissue damage at the site of injection. Additionally, adjuvant and Map antigen distribution throughout the granulomatous inflammatory infiltrate, as well as the NRAMP1 cell expression, which is linked to antigen phagocytosis, were highly irregular. In Silirum® induced granulomas, a higher number of MHC-II and TNF-expressing cells and a lower number of M2 macrophages suggested an improved antigen presentation, which could be due to the better antigen distribution and reduced tissue damage induced by this vaccine.